Front-End Monitoring of Multiple Loads in Wireless Power Transfer Systems Without Wireless Communication Systems - Yin,J; Lin,D; Lee,CK; Parisini,T; Hui,SYR (IEEE Transactions on Power Electronics, 2015)
This paper describes a method for monitoring multiple loads from the front end of a wireless power transfer system without using any wireless communication systems. A mathematical approach based on scanning the frequency around the resonant frequency has been developed for deriving the load conditions. The proposal requires only information of the input voltage and current, thereby eliminating the requirements of using wireless communication systems for feedback control. The proposal has been practically confirmed in hardware prototype with good results.